Insulin resistance is related with oxidative stress in systemic lupus erythematosus - Koca, Suleyman Serdar; Karaca, Ilgin; Yavuzkii, Mustafa Ferzeyn; Dagli, Necati; Ozgen, Metin; Ustundag, Bilal; Isik, Ahmet (Kare Publ, 2009)
Objective: Systemic lupus erythematosus (SLE) patients have increased risk of coronary heart disease (CHD) that cannot be fully explained by the traditional risk factors. Metabolic alterations like oxidative stress and insulin resistance may be additional risk factors to contribute early and accelerated atherosclerosis in SLE. Our aim was to evaluate malondialdehyde (MDA) level, oxidative stress indicator, and homeostasis model assessment of insulin resistance (HOMA-IR), and possible relationship between oxidative stress and insulin resistance, in SLE. Methods: This cross-sectional controlled study included 30 SLE patients (SLE group) and 15 age- and sex-matched healthy controls (HC group). The SLE patients were classified into subgroups based on the disease activity index as active or inactive. Serum MDA, insulin, C-peptide, fasting blood glucose, lipid profile, acute phase reactants, tumor necrosis factor (TNF)-alpha, interleukin (IL)-6 and HOMA-IR were determined. Statistical analyses were performed using Kruskal-Wallis, Mann-Whitney U and Pearson tests. Results: In the SLE group, TNF-alpha (7.9 [0.5-57.8] vs. 3.9 [0.3-6.3] pg/ml, p<0.01), IL-6 (9.2 [0.1-33.9] vs. 2.2 [0.1-4.8] pg/ml, p<0.01), MDA (2.3 [0.1-6.7] vs. 0.95 [0.5-2.96] nmol/ml, p<0.01) and C-peptide (1.9 [0.9-3.5] vs. 1.5 [1.1-2.4] ng/ml, p<0.01) levels were higher than in the HC group, while HOMA-IR index (1.7 [0.5-6.5] vs. 1.2 [0.8-2.9], p>0.05) was nonsignificantly higher. In the SLE group, MDA levels were correlated with insulin (r=0.614, P<0.05) and HOMA-IR (r=0.601, p<0.05). Conclusion: In inflammatory diseases, relations between oxidative stress and insulin resistance, each of them triggers or enhances the other one, come to an impasse. In conclusion, this modifiable impasse might be important to prevent the development of atherosclerosis in SLE. (Anadolu Kardiyol Derg 2009; 9: 23-8)
Keywords: Insulin resistance; HOMA-IR; oxidative stress; malondialdehyde; inflammation; systemic lupus erythematosus